INTERACTIVE DIGITAL MATH MEDIA FOR ENHANCING ELEMENTARY STUDENTS’ LEARNING OUTCOMES - Putri Mayadesti; Henrizal; Merri Yeliza (Jurnal Cakrawala Pendas, 2025)
This study aims to develop an interactive learning media called Digital Math Learning and test its validity, practicality, and effectiveness in improving elementary school students' mathematics learning outcomes. This study is based on students' low understanding of mathematical concepts influenced by the limited variety of learning media used by teachers, so that the learning process tends to be monotonous and lacks active student participation. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects included experts, teachers, and students. Data were collected through observation, questionnaires, tests, interviews, and documentation, and analyzed using the validity, practicality, and effectiveness of the learning media. The results showed that the developed interactive learning media, Digital Math Learning, met the criteria for validity, practicality, and effectiveness. Expert validation in terms of content, media, and language produced an overall score categorized as very valid, indicating that the media is feasible for instructional use. Practicality testing also showed a very practical category, as teachers and students found the media easy to use, engaging, and relevant to elementary learners’ needs. In terms of effectiveness, the learning outcomes demonstrated a significant improvement, with an N-Gain score of 0.80 (high category) and a student response rate of 96.08% (very effective category). Digital Math Learning effectively enhances conceptual understanding and student engagement and has the potential to become an interactive and adaptive digital learning solution aligned with learning styles and cognitive abilities.